Understanding the University Students’ Outcome Expectations by Using a Professional Networking Site: The Theory of Social Cognitive - Siew Wei Jie; Siti Aisyah Binti Hazarinan; Siti Aisyah Binti Ramli; Siti Nur Aliah Binti Zaidan; Thoriq Luqmansyah; Ujvalkumar Rajendra Jadhav; Akchhay Kant Jha (Asia Pacific Journal of Management and Education (APJME), 2024)
Recently, many university students have utilized LinkedIn to their advantage and launched their professional careers. This research attempts to ascertain the relationship between university students’ attitudes, intentions, self-efficacy (independent variables), and outcome expectation (dependent variable). There were 157 respondents in the sample, but only 144 replies were valid. An online survey was used to obtain the data for this cross-sectional research. The survey data were calculated and analyzed using the Statistical Package for Social Science (SPSS). Results show that self-efficacy and intention significantly influence outcome expectations. Specifically, self-efficacy had a strong positive effect (? = 0.503, p 0.001), while intention also positively impacted outcome expectations (? = 0.316, p 0.001). However, students' attitudes toward LinkedIn did not significantly affect outcome expectations (? = 0.141, p 0.05), leading to the rejection of the hypothesis regarding attitude. These findings indicate that students' confidence in their abilities and their purposeful engagement with LinkedIn are more influential in shaping positive outcomes than their general attitudes toward the platform. To improve student outcomes, universities, and career services should focus on developing students' self-efficacy and LinkedIn skills.